Iron deficiency in distance runners. A reinvestigation using Fe-labelling and non-invasive liver iron quantification - Nachtigall, D.; Nielsen, P.; Fischer, R.; Engelhardt, R.; Gabbe, E. E. (International Journal of Sports Medicine, 1996)
In a group of male distance runners, 23 out of 45 athletes showed decreased serum ferritin values (< 35 micrograms). The high prevalence of a typical iron deficiency in runners was confirmed in a subgroup of eight athletes in which the iron metabolism was studied in detail using radio-iron labelling and liver iron quantification. Most of these athletes showed an up-regulated 59Fe absorption and a decreased liver iron concentration as compared to a control group. 59Fe activity in collected samples of stool, urine or sweat was measured sensitively using a shielded high-pure germanium spectrometer. In periods without running, a faecal excretion of 59Fe equivalent to 1.5 ml blood loss/d was observed, which represents the normal iron excretion. Under intensive training or racing conditions, a significant increase up to 4.9-6.6 ml blood loss/day was observed, whereas excretion of 59Fe in urine or sweat was negligible. Thus, gastrointestinal blood loss was the main reason for the slightly negative iron balance in the runners. This confirms earlier studies in the literature using qualitative blood stool testing. A treatment with 100 mg ferrous iron/day for 3 months significantly increased the values for serum ferritin (from 34 +/- 11 to 54 +/- 18 micrograms/l) and liver iron (from 105 +/- 42 to 227 +/- 67 micrograms/g liver).